PENERAPAN PENDIDIKAN KARAKTER DALAM KEGIATAN KEAGAMAAN DI MASYARAKAT: PERSPEKTIF MANAJEMEN PENDIDIKAN ISLAM - Setiabudi, Dede Indra; Galih Permana; Irvan Destian; Aan Hasanah; Bambang Samsul Arifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research employs a library research approach to explore the perspective of Islamic education management in implementing character education through religious activities in society. By reviewing relevant literature, this study analyzes strategies, the role of religious figures, and challenges in implementing character education with a focus on the Islamic context. Findings indicate that the application of character education in religious activities requires good coordination between formal and informal educational institutions, as well as active support from religious figures in conveying character values. However, challenges such as cultural resistance and resource limitations also affect the effectiveness of implementation. Through the library research approach, this study provides in-depth insights into efforts to implement character education in the context of religious activities in society and highlights directions for further research to strengthen and broaden understanding in this field. Keywords: Character Education, Society, Islamic Education Management;